Application of high resolution microscopy and optical spectroscopy for study of phase separation in phosphorus- and fluorine-containing sodium borosilicate glasses - Antropova, Tatyana V.; Drozdova, Irina; Kukhtevich, Igor; Evstrapov, Anatoly; Esikova, Nadya (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The kinetics of phase separation in glass-forming Na2O–B2O3–SiO2–P2O5–|F| system and structure parameters of the two-phase glasses have been investigated by transmission electron microscopy (TEM) and optical spectroscopy methods. The TEM images were analyzed with the help of specially designed software for the purpose of determination of the relative volume and size of the phases. An influence of duration of a glass heat treatment on the parameters of their structure was investigated at a temperature of 550 °C which is necessary for prompting a two-network structure and is most frequently used for manufacturing porous glasses. The time of glass heat treatment necessary for achieving phase equilibrium was established. A deviation of the phase inhomogeneity growth rate from theoretical one was determined. It was revealed that a certain third phase, the composition of which can include α-quartz, is formed in glass during the heat treatment. Fluorescence of the two-phase glass which has been subjected to heat treatment for a long time can be caused by the presence of this phase.
Optica Applicata, Vol. 40, 2010, nr 2, s. 293-304
Keywords: optyka; alkali borosilicate glasses; phase separation; transmission electron microscopy; optical spectroscopy